The association between Vitamin D deficiency and clinical pregnancy rate in IVF patients with different age - Wang, Keyan; Dong, Fangli; Ma, Shuxia; Bu, Zhiqin (Frontiers in Endocrinology, 2025)
BackgroundThe aim of the present study was to investigate the impact of serum VD status on IVF outcomes and to observe the effect of VD deficiency on the expression of the endometrial receptivity marker HOXA10.Materials and methodsPatients undergoing their first IVF cycles were divided into 3 groups according to VD levels (deficient: <20 ng/mL, insufficient: 20-29.9 ng/mL), and replete ≥30 ng/mL). IVF laboratory parameters, implantation rate, and clinical pregnancy rate were compared among these groups according to patient age (≥ 35 years old and < 35 years old). In addition, the expression of HOXA10 was analyzed using quantitative RT-PCR (qRT-PCR) and western blot in mRNA and protein levels, respectively.ResultsA total of 1459 patients were included. Clinical pregnancy outcomes were significantly worse in vitamin D-deficient patients of advanced age than in other patients. VD status was a predictor of clinical pregnancy according to the multivariate regression model (Deficient: OR = 0.74, 95% CI: 0.59-0.90, P = 0.022; Insufficient: OR = 0.85, 95% CI: 0.70-1.10, P = 0.104; Reference = Replete). However, clinical pregnancy outcomes were comparable among the three groups of young patients. Endometrial tissue was collected from a total of 35 women. HOXA10 expression was significantly lower only in young women in the vitamin D deficiency group. Furthermore, among patients of advanced age, HOXA10 levels were significantly decreased in both vitamin D-deficient and vitamin D-insufficient women.ConclusionVD deficiency appears to lead to poorer clinical pregnancy outcomes in patients of advanced age. In the future we can observe whether pregnancy outcomes can be improved in such patients with vitamin D supplementation. In addition, a possible explanation for the worse results may be the detrimental effect of reduced HOXA10 expression on endometrial receptivity.